ROCK QUALITY GROUPING IN SANDSTONE FORMATION USING A CRITICAL POROSITY APPROACH AT FORMATION PRESSURE CONDITIONS - Sigit Rahmawan; Ghanima Yasmaniar; Suryo Prakoso (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2020)
The methods of grouping reservoir rock types based on the physical properties of rocks that have been studied by previous researchers still have a relatively large value of uncertainty. This uncertainty arises in conditions where rock type grouping is carried out in wells that do not have core sample data. Where we know that in the oil and gas field, not all wells in the field are subjected to rock sampling, either routine core analysis or special core analysis. From these problems, the authors feel the need to carry out this study to create a method for classifying reservoir rock types based on the physical properties of rocks that can be used in wells that do not have core sample data. The rock types in the wells that do not have core samples will be grouped based on the critical porosity value of the rock obtained from the vp value in the acoustic log data owned by these wells. By making an approach model through the critical porosity of rocks from wells that have core sample data, wells that only have acoustic log data can be grouped by using the critical porosity approach which is generated from the vp value of the acoustic log.